Efektivitas Program Kartu Identitas Anak (KIA) di Dinas Kependudukan dan Pencatatan Sipil Kota Semarang - Larasati, Hanandha; Maesaroh, Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The provision of population identity for all Indonesians nationally is an effort that the government makes in order to provide the fulfillment of constitutional rights and protection as citizens, but children do not yet have an official identity such as ID cards owned by adults. The government through the Ministry of Home Affairs of the Republic of Indonesia then issued the Regulation of the Minister of Home Affairs Number 2/2016 concerning Child Identity Cards (KIA) in order to increases population data collection, provide protection and fulfilment of constitutional rights, and increases public services for children under the age of 17 years old which is integrated with the Population Administration Information System (SIAK). It is purposes for the child in getting the services independently and in terms of administrative completeness. This study uses qualitative descriptive methods with documentation techniques, literature, and key informant interviews with snowball sampling and representatives communities with accidental sampling. The use of theory to answer research problems is Duncan's theory with the criteria of effectiveness of achieving goals, integration, and adaptation with the aim of analyzing the effectiveness of the KIA program in the Department of Civil Service and Civil Registration of Semarang City as well as inhibition factors of the implementation of the KIA program. The results showed that the effectiveness of KIA program in achieving goals and integration has not fully run optimally, while adaptation has been able to run well. This is influenced by the inhibiting factors, namely environmental conditions due to the view that children are still dependent on their parents, it is still difficult to reach underprivileged families, the lack of information about the uses and benefits of KIA, and complicated bureaucracy. Recommendations that can be given are to improve all forms of understanding of KIA through socialization, increases promotion and cooperation with the partners in a sustainable manner, as well as adding ease of service with mobile cars to increase KIA's ownership in Semarang City.